Peritoneal histopathological changes and cultures after autogenous fecal peritonitis induced in elderly rat model: response to intravenous use of meropenem and intra-abdominal inoculation of 10% aqueous extract of Schinus Terebinthifolius Raddi (Anacardiaceae) - Carlos Alberto Figueiredo Filho; Celia Maria Machado Barbosa Castro; Guilherme Veras Mascena; Gustavo Ithamar Souto Maior; Tharcia Kiara Beserra Oliveira; Valéria Wanderley Pinto Brandão Marquis; Carlos Teixeira Brandt (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To evaluate the peritoneal histopathological changes and culture after the use of intravenous meropenem and intra-abdominal inoculation of 10% aqueous extract of anacardiaceae, in elderly rat model after autogenous fecal peritonitis induced. Methods: Thirty 18-month-old Wistar rats received induction of autogenous fecal peritonitis and then were stratified into two groups: study I, treated with meropenem (40 mg/kg); and study II, treated with meropenem (40 mg/kg) and intraperitoneal 10% aqueous extract of anacardiaceae. Animals were monitored for 15 days until euthanasia. Peritoneal fragments were collected for histopathological and culture. The study was approved by Ethics Committee. Results: None study-II animals died, while in study I, one died before euthanasia. In study II, 20% of the animals showed histopathological changes, none positive peritoneal culture, but one blood culture was positive (10%). In study I, 50% of the animals presented histopathological changes, 40% positive peritoneal cultures, and 50% positive blood cultures. All results when evaluated in the morbidity score showed better outcome for study-II group (p = 0,175). Conclusion: The use of meropenem associated with intraperitoneal 10% aqueous anacardiaceae extract after induction of autogenous fecal peritonitis in elderly rats showed better outcome in the set of histopathological changes, negative peritoneal and blood cultures, when compared with the use of meropenem isolated.